Komunikasi dan Kebudayaan Islam di Indonesia - Ahmad Yadi (Kalijaga Journal of Communication, 2020)
This study tries to explore the link between communication and Islamic culture in Indonesia. To see the linkages, the authors used research with a library research method which focused three issues, namely first, the relationship between communication and culture; second, the relationship between culture and religion; and thirdly, the institutionalization of Islamic cultural values in Indonesia. The results of the study turned out that communication and culture are two things that are inseparable. If we talk about communication then we also talk about culture. Religion and culture are closely related and complementary such as the influence of Islam on culture and cultural influence on Islam. Therefore we know the term "Islamization of culture and the teaching of Islam". Institutionalization of Islamic values is very strong in shaping the system of knowledge and intellectuality of society, belief system, national culture, economic system and the formation of the behavior of Muslims in Indonesia. In short, Islamic values have been rooted in Indonesia national culture.Studi ini mencoba untuk mengeksplorasi keterkaitan antara komunikasi dan budaya Islam di Indonesia. Untuk melihat keterkaitan tersebut, penulis menggunakan penelitian dengan metode penelitian pustaka yang mana memfokuskan tiga isu yaitu pertama, hubungan antara komunikasi dan budaya; kedua, hubungan antara budaya dan agama; dan ketiga, institusionalisasi nilai-nilai budaya Islam di Indonesia. Hasil studi yang dilakukan ternyata komunikasi dan budaya adalah dua hal yang tak terpisahkan. Jika kita membicarakan komunikasi berarti kita juga bicara tentang budaya. Agama dan budaya memiliki kaitan yang erat dan saling melengkapi misalnya pengaruh Islam terhadap budaya dan pengaruh budaya terhadap Islam. Oleh karena itu kita mengenal istilah “Islamisasi budaya dan mengadabkan Islam”. Institusionalisasi nilai-nilai Islam sangat kuat dalam membentuk sistem pengetahuan dan intelektualitas masyarakat, system kepercayaan, budaya nasional, sistem ekonomi dan pembentukan perilaku umat Islam di Indonesia. Pendeknya nilai-nilai Islam telah mengakar ke dalam budaya nasional Indonesia.